Indoloparacyclophanes: Synthesis and Dopamine Receptor Binding of a Novel Arylbioisostere - Waibel, Reiner; Gmeiner, Peter; et al. (Angewandte Chemie International Edition, 2001)
Fancy drug candidates: The first preparation of indoloparacyclophanes is reported through the use of the Buchwald variant of the Fischer indole synthesis (see scheme). Receptor binding studies clearly demonstrated that the double-layered molecular scaffold can serve as an effective arylbioisostere.
UnivIS-Import:2015-03-09:Pub.2001.nat.dchph.lphch.indolo
Keywords: Bioisosteres; Cylophanes; Fischer indolization; Indoles; Receptors